2014
DOI: 10.1371/journal.pone.0095537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transgenic Cry1Ac + CpTI Cotton on Non-Target Mealybug Pest Ferrisia virgata and Its Predator Cryptolaemus montrouzieri

Abstract: Recently, several invasive mealybugs (Hemiptera: Pseudococcidae) have rapidly spread to Asia and have become a serious threat to the production of cotton including transgenic cotton. Thus far, studies have mainly focused on the effects of mealybugs on non-transgenic cotton, without fully considering their effects on transgenic cotton and trophic interactions. Therefore, investigating the potential effects of mealybugs on transgenic cotton and their key natural enemies is vitally important. A first study on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Bt protein concentrations in cotton leaves, insect prey and predator were measured, using sandwich ELISA, using quantiplate kits (Wu et al 2014). The concentration of Cry1Ac protein was measured, using Cry 1Ab/ Cry1Ac kit (AP 003 QT V50) and Cry2Ab using Cry2A kit (AP 005 QT BC V50) of ENVIROLOGIX 500 Riverside Industrial Parkway Portland, ME, USA.…”
Section: Elisa Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Bt protein concentrations in cotton leaves, insect prey and predator were measured, using sandwich ELISA, using quantiplate kits (Wu et al 2014). The concentration of Cry1Ac protein was measured, using Cry 1Ab/ Cry1Ac kit (AP 003 QT V50) and Cry2Ab using Cry2A kit (AP 005 QT BC V50) of ENVIROLOGIX 500 Riverside Industrial Parkway Portland, ME, USA.…”
Section: Elisa Proceduresmentioning
confidence: 99%
“…Simon et al (2006) reported that Cry1Ab or Cry2Ab toxins did not have detrimental effects on C. carnea when ingested either directly or through prey as the larval midgut lacks specific receptors for these proteins. No prey-mediated effects of Cry proteins have also been reported in other predatory species including the coccinellids (Wu et al 2014), the rove beetles (Garcia et al 2010) and the wolf spiders (Niu et al 2017).…”
Section: Development Survival and Weight Of C Zastrowi Sillemi Fed mentioning
confidence: 99%
“…Evolution of resistance to a single trypsin inhibitor in populations of pest insects could be a problem for successful implementation of transgenic plants. It can be overcome by the use of genes for multifunctional inhibitors (Luo et al., ) and fusion proteins (Sainsbury et al., ) or by pyramiding genes (Dunse et al., ; Senthilkumar et al., ; Liu et al., ; Diaz & Santamaria, ; Wu et al., ). Understanding the adaptive responses of pest insects contributes to selection of the appropriate combination of digestive enzyme inhibitors (Dunse et al., ; Spit et al., ).…”
Section: Trypsin As a Target Of Pest Controlmentioning
confidence: 99%
“…Despite concern that transgenic plants may affect non‐target organisms, negative effects of trypsin inhibitors on other herbivores and natural enemies of pest insects have rarely been recorded under field conditions due to low expression of insecticidal proteins and/or adaptive responses of parasitoids and predators (Schlüter et al., ). If there are no negative effects on natural enemies or if a plant is transformed with an inhibitor of proteases not present in their gut (Álvarez‐Alfageme et al., ; Wu et al., ), then application of methods of biological control may provide additional protection of transgenic plants and delay evolution of resistant pests.…”
Section: Trypsin As a Target Of Pest Controlmentioning
confidence: 99%
“…'Prey quality-mediated effects' can be avoided in experiments by using a herbivore that is not susceptible to the plantexpressed Cry toxins (i.e., a non-susceptible herbivore) or by using a strain of the target organism that is highly resistant to the particular toxin (i.e., a Bt-resistant herbivore). The use of a non-susceptible herbivore or a Bt-resistant herbivore ensures that the herbivores themselves are not adversely affected by the ingested toxin (Chen et al, 2008;Lawo et al, 2010;Li et al, 2011;Tian et al, 2014;Wu et al, 2014;Su et al, 2015).…”
Section: Introductionmentioning
confidence: 99%